Electrical Stimulation for Children with Cerebral Palsy: A Meta-analysis for Randomized Controlled Trials - Liu, Yu; Li, Hongzhi (Neuropediatrics, 2023)
Background Different types of electrical stimulation (ES) showed diverse effects on children with cerebral palsy (CP). Previous studies reported inconsistent results for effects of ES on children with CP. The present study aimed to conduct a meta-analysis to summarize these diverse results.Methods We searched for studies exploring effects of ES on children with CP in databases (PubMed and Web of Science) from their inception until December 2022. Standard mean differences (SMDs) and 95% confidence intervals (CIs) were computed using STATA 12.0 software.Results The meta-analysis included 19 randomized controlled trials (including 265 CP patients in test group and 263 CP patients in corresponding control group). The study showed an increased improvement in gross motor function, walking speed, step length, and daily living activities in ES group compared with corresponding control group with random effects models (gross motor function: SMD = 2.04, 95% CI = 1.43–2.65; walking speed: SMD = 3.71, 95% CI = 1.49–5.92; step length: SMD = 1.89, 95% CI = 0.65–3.13; daily living activities: SMD = 5.18, 95% CI = 3.04–7.31), whereas the study showed no significant difference in change of muscle strength between ES group and the corresponding control group with a random effects model (SMD = 0.42, 95% CI = −0.12 to 0.97).Conclusion The study demonstrated that ES might be used as therapy to improve gross motor function, gait, and daily living activities in children with CP.
Keywords: cerebral palsy; electrical stimulation; functional electrical stimulation; meta-analysis; neuromuscular electrical stimulation